2020
DOI: 10.1590/1519-6984.193388
|View full text |Cite
|
Sign up to set email alerts
|

Eggs of tegu lizard, Salvator merianae (Duméril & Bilbron, 1839) (Squamata; Teiidae) damaged by fungal infections

Abstract: Abstract The tegu (Salvator merianae) is the largest lizard found in Brazil and has a wide distribution, occurring in several biomes. The presence of fungi on reptilian eggs initially occurs on infertile eggs, which leads to a subsequent infection in fertile eggs, causing damage and death of embryos. The objective of this study was to identify the fungi that caused lesions in the eggs of tegu in captivity. Swabs were collected on infected and healthy eggshells, in an embryo that died and the substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…For example, a recent study reports that fungal infections in eggs of tegu lizards Salvator merianae (Duméril & Bilbron, 1839) can cause damage and death of their embryos (Carvalho et al, 2020). Moreover, a study performed by Santana-Neto et al (2010) showed that filamentous fungi may have a role in the regulation of field scorpion populations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study reports that fungal infections in eggs of tegu lizards Salvator merianae (Duméril & Bilbron, 1839) can cause damage and death of their embryos (Carvalho et al, 2020). Moreover, a study performed by Santana-Neto et al (2010) showed that filamentous fungi may have a role in the regulation of field scorpion populations.…”
Section: Introductionmentioning
confidence: 99%